Tailored Ag–Cu–Mg multielemental nanoparticles for wide-spectrum antibacterial coating. Issue 4 (15th January 2019) - Benetti, Giulio; Cavaliere, Emanuele; Brescia, Rosaria; Salassi, Sebastian; Ferrando, Riccardo; Vantomme, André; Pallecchi, Lucia; Pollini, Simona; Boncompagni, Selene; Fortuni, Beatrice; Van Bael, Margriet J.; Banfi, Francesco; et al.
Abstract : Bactericidal nanoparticle coatings are very promising for hindering the indirect transmission of pathogens through cross-contaminated surfaces. Abstract : Bactericidal nanoparticle coatings are very promising for hindering the indirect transmission of pathogens through cross-contaminated surfaces. The challenge, limiting their employment in nosocomial environments, is the ability of tailoring the coating's physicochemical properties, namely, composition, cytotoxicity, bactericidal spectrum, adhesion to the substrate, and consequent nanoparticles release into the environment. We have engineered a new family of nanoparticle-based bactericidal coatings comprising Ag, Cu, and Mg and synthesized by a green gas-phase technique. These coatings present wide-spectrum bactericidal activity on both Gram-positive and Gram-negative reference strains and tunable physicochemical properties of relevance in view of their "on-field" deployment. The link between material and functional properties is rationalized based on a multidisciplinary and multitechnique approach. Our results pave the way for engineering biofunctional, fully tunable nanoparticle coatings, exploiting an arbitrarily wide number of elements in a straightforward, eco-friendly, high-throughput, one-step process.